(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2024)
This study explores the convergence of spirituality and leadership skills in the sphere of sustainable management. Spirituality is considered an essential element that establishes a connection between individuals and both a higher power and ultimate truth. Spirituality, when linked with leadership qualities, strengthens contemporary management ideas, and practices, and explores how leaders might utilize spiritual ideas to efficiently fulfill their tasks and obligations, therefore promoting sustainability within businesses. The growing focus on sustainability, driven by corporate scandals and global economic crises, highlights the need for a comprehensive approach that incorporates skills, spirituality, and their significance in management. This research highlights the significance of empowered leadership and moral authority in promoting sustainable management practices, drawing on evidence from social psychology and leadership studies. Leaders that possess spiritual qualities are more capable of inspiring and motivating their teams. This results in the establishment of a favourable organizational culture that places a high value on ethical conduct and long-term achievement. Further, this study explores the notion of workplace spirituality, which is described as a feeling of purpose and interconnectedness among employees, and its influence on organizational dynamics. The results indicate that combining leadership skills with spirituality leads to enhanced and morally upright leadership, which promotes culture of trust, collaboration, and organizational success, and include spirituality into their leadership practices. They establish cultures that foster innovation, promote employee well-being, and enhance overall organizational resilience, who can effectively address difficult challenges and achieve sustainable growth and stability by incorporating spiritual principles into their decision-making process.